KADAR MEAN CORPUSCULAR VOLUME (MCV) PADA PENGGUNA ALKOHOL MENAHUN DI DESA RURUKAN KECAMATAN TOMOHON TIMUR - Mokoagow, Nanang A.; Supit, Siantan; Polii, Hedison (Universitas Sam Ratulangi, 2015)
Abstract: Chronic consumption of alcohol in large enough quantity can cause a variety of health problems, one of them is anemia. Maximum blood alcohol level is achieved in 30-90 minutes. This study aimed to obtain the level of Mean Corpuscular Volume (MCV) among alcohol consumers in Rurukan village, Tomohon. This was a descriptive study with a cross sectional design. The level of MCV was measured by using ABX tool Petra XL 80. The results showed that there were 30 respondents in this study. Most of the respondents were in age group 46-55 years (63%), worked as labours/motor drivers (80%), and the durations of alcohol consumption were 7-10 years and 11-15 years with an average of MCV level of 88.62 fL (within normal limit). Conclusion: The average of MCV level of chronic alcohol consumers in Rurukan village, Tomohon, was still within normal limit.Keywords: chronic alcohol consumption, MCVAbstrak: Penggunaan alkohol yang lama dan dalam jumlah cukup besar dapat menimbulkan berbagai masalah kesehatan, salah satunya anemia. Kadar alkohol maksimum dalam darah dicapai 30-90 menit. Penelitian ini bertujuan untuk mengetahui gambaran kadar MCV pada pengguna alkohol menahun di Desa Rurukan Kecamatan Tomohon Timur. Penelitian ini bersifat deskriptif dengan rancangan potong lintang. Pemeriksaan kadar MCV menggunakan alat BAX Petra XL 80. Hasil penelitian memperlihatkan dari 30 responden yang terbanyak terdapat pada kelompok umur 46-55 tahun (63%), pekerjaan sebagai buruh/ojek (80%), dan lama mengonsumsi alkohol 7-10 tahun dan 11-15 tahun dengan rerata kadar MCV 88,62 fL (dalam batas normal). Simpulan: Rerata kadar MCV pengguna alkohol menahun di Desa Rurukan Kecamatan Tomohon Timur masih dalam batas normal.Kata kunci: konsumsi alkohol menahun, MCV